2007
DOI: 10.1186/1749-7922-2-13
|View full text |Cite
|
Sign up to set email alerts
|

The effect of erythropoietin on healing of obstructive vs nonobstructive left colonic anastomosis: an experimental study

Abstract: We failed to find any direct and evident effects of erythropoietin on healing of left colonic anastomosis. On the other hand, erythropoietin might prevent negative effects of obstruction on healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Various agents have been investigated to ameliorate these effects of peritonitis on colonic anastomoses. All of these agents aiming to reduce ischemia including hyperbaric oxygen, glucan, erythropoietin, bosentan, growth hormone, and H 2 antagonists like famotidine [10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Various agents have been investigated to ameliorate these effects of peritonitis on colonic anastomoses. All of these agents aiming to reduce ischemia including hyperbaric oxygen, glucan, erythropoietin, bosentan, growth hormone, and H 2 antagonists like famotidine [10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…These agents include hyperbaric oxygen, glucan, erythropoietin, bosentan, growth hormone, and H 2 antagonists like famotidine. All of these agents aim to reduce ischemia (18)(19)(20)(21)(22)(23). OT increases tissue oxygenation by shifting the oxyhaemoglobin curve to the right.…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of this complication has been significantly reduced with the application of modern surgical techniques, it is still an important complication. [4,9,[12][13][14] As with all anastomoses, tissue blood flow and oxygenation are considerable factors in colonic anastomoses. [5,12] In comparison with other gastrointestinal components, the colon is known to present higher anastomotic leak rates due to its certain anatomical and biological characteristics, such as low collagen content, high collagenase activity, reduced collateral circulation, and absence of a serosa in the extraperitoneal rectum.…”
Section: Discussionmentioning
confidence: 99%
“…The common denominator of all those studies was the effort to reduce ischemia. [4,5,12,14,16,17] Benacerraf et al [18] reported 100% anastomotic leak in cases where perianastomotic oxygen pressure was below 20 mmHg, while denoting that the anastomotic leak rate was reduced by elevation of oxygen pressure. In the current study, we used pentoxifylline and vinpocetine to reduce ischemia.…”
Section: Discussionmentioning
confidence: 99%